Prognostic potential of proliferative activity index in assessing the effectiveness of complex neoadjuvant treatment of locally advanced breast cancer - Bondar, O. V. (Journal of Education, Health and Sport, 2019)
In recent years, breast cancer (breast cancer) has been the most common cancer and the most common cause of disability among women in developed countries. The aim of the study - determination of the role of Ki-67 and PCNA nuclear markers for the evaluation and prediction of the effectiveness of neoadjuvant antitumor treatment with the use of polychemotherapy in systemic (SPHT), endolymphatic (ELPHT) and selective intra-arterial (SIAPHT) variants in patients with breast cancer. The study was conducted on the basis of materials from 90 histories of in patients with LABC luminal type B Т4А-DN0-2М0. The total sample was divided into three subgroups by parameter of route of neoadjuvant polychemotherapy (PCT): first control group, 22 patients - systemic PCT; the second control group (27 patients) - endolymphatic PCT; study group (41 patients) - selective intra-arterial PCT. Clinical effect with qualitative changes of local status and transfer of patients to the category of those with resectable tumors appeared in 46% of women of the first control group after 6 courses of SPCT, in 59% of the second control group after 4 courses of ELPCT and in 90% of the studied group after 3 courses SIAPCT. After systemic and endolymphatic PCT, reductions in Ki-67 and PCNA levels were determined to be insignificant (p>0.05) by the Mac-Nemar criterion χ2. For selective intra-arterial techniques, the dynamics were considered significant (p <0.05). Intergroup comparisons revealed a statistical advantage in favor of the third group for Pearson’s χ2 compared to the first and second ones. In the study of the association between the fact of radical surgery and the initial marker levels, a strong prognostic property of Ki-67 and PCNA was determined up to 25% with respect to the outcome of future comprehensive treatment. With the use of SIAPCT in the non-adjuvant treatment of breast cancer by Ki-67 and PCNA in the range of up to 25%, the tumor responds significantly better to the therapy and reaches a resectable status in a statistically significantly greater proportion in patients with LABC.